Temporary custody; Criminality; Human rights; Impunity; Torture - de la Barreda Solórzano, Luis (2016)
This article is about a pair of factors that cause the distress that can be observed within the mexican society: the overflowed criminality and the impunity, by virtue of which the State is not fullfiling its essential historical duty: to provide an aceptable level of public security. This has two sources that complement each other. One is the sensation we get when we face an unpredictable threat. It is caused by crime. The other is defencelessness or knowing that we can only rely in our own strength because there is no one willing to protect or assist us.